Gene therapy in sports medicine - Lamsam, C.; Fu, F. H.; Robbins, P. D.; Evans, C. H. (Sports Medicine, 1998)
Sports injuries frequently involve tissues that have limited healing capabilities. In order to improve the healing process and thus prevent the serious consequences of injury, it is necessary to understand the molecular and cellular biology of healing. Several growth factors and other cytokines have been identified as important mediators of a successful healing process. Such molecules have promise as novel agents for the treatment of sporting injuries, but there is presently no clinically useful way to deliver them. Gene transfer may be used to serve this purpose. In this role, gene therapy functions as a type of local biological drug delivery system. Recent studies have shown the feasibility of transferring marker genes to synovium, chondrocytes, meniscal fibrochondrocytes, tenocytes and ligamental fibroblasts, prompting optimism about the eventual success of this approach.